2023
DOI: 10.1002/jeq2.20443
|View full text |Cite
|
Sign up to set email alerts
|

Microbial source tracking and land use associations for antibiotic resistance genes in private wells influenced by human and livestock fecal sources

Abstract: Antimicrobial resistance is a growing public health problem that requires an integrated approach among human, agricultural, and environmental sectors. However, few studies address all three components simultaneously. We investigated the occurrence of five antibiotic resistance genes (ARGs) and the class 1 integron gene (intI1) in private wells drawing water from a vulnerable aquifer influenced by residential septic systems and land‐applied dairy manure. Samples (n = 138) were collected across four seasons from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 115 publications
0
5
0
1
Order By: Relevance
“…As for the sample type, there was no significant difference ( p < 0.05) in the occurrence of AMR between the isolates obtained from WWTPs (3.97 ± 1.66) and those collected from drainage water in areas of different land uses (3.72 ± 0.98). Likewise, Burch et al [ 21 ] indicated the co-occurrence of AMR genes in groundwater with human fecal sources at similar rates. Consistent with the high occurrence of AMR in the bacteria isolated from water in areas of multiple land use and from WWTPs, several scientists [ 6 , 22 , 23 , 24 , 25 ] indicated that surface waters receive WWTP effluents as well as run-off from manure-fertilized fields and animal feeding operations containing antibiotic resistance genes and serve as a central hub for the transport and dissemination of AM-resistant bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the sample type, there was no significant difference ( p < 0.05) in the occurrence of AMR between the isolates obtained from WWTPs (3.97 ± 1.66) and those collected from drainage water in areas of different land uses (3.72 ± 0.98). Likewise, Burch et al [ 21 ] indicated the co-occurrence of AMR genes in groundwater with human fecal sources at similar rates. Consistent with the high occurrence of AMR in the bacteria isolated from water in areas of multiple land use and from WWTPs, several scientists [ 6 , 22 , 23 , 24 , 25 ] indicated that surface waters receive WWTP effluents as well as run-off from manure-fertilized fields and animal feeding operations containing antibiotic resistance genes and serve as a central hub for the transport and dissemination of AM-resistant bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Doyle et al [ 35 ] also indicated that this variability might be due to substantive differences in antimicrobial usage and practices. While Hernando-Amado et al [ 36 ] reported that contributing factors to the incidence of AMR in bacteria span the One Health spectrum, including human, agricultural, and environmental dimensions, several scientists [ 37 , 38 , 39 , 40 ] reported that the antimicrobial use in human medicine and livestock production contributes to the emergence of bacteria carrying AMR, and AM-resistant bacteria excreted in feces can be transported through environmental compartments, including soil, water, and air [ 21 ]. In addition, a CDC report [ 41 ] indicated that AMR germs and genes that cause resistance traits are present in the environment and can spread in waterways and soils.…”
Section: Resultsmentioning
confidence: 99%
“…Co-occurrence of human and agricultural fecal sources in rural areas further complicates the attribution of ARB and ARG to septic systems [ 33 , 34 ], as farm animals are also a significant source of resistance elements and organisms to the environment [ 35 ]. Associations between the presence or abundance of human fecal indicators and ARG and/or resistant isolates are therefore commonly used to establish these links [ 32 , 34 , 36 ]. Burch et al found that detection of the ARG sul 1, tetA , and tetX and the integron intl 1 in well water was significantly correlated to the number of septic systems within the drainage area [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between the presence or abundance of human fecal indicators and ARG and/or resistant isolates are therefore commonly used to establish these links [ 32 , 34 , 36 ]. Burch et al found that detection of the ARG sul 1, tetA , and tetX and the integron intl 1 in well water was significantly correlated to the number of septic systems within the drainage area [ 34 ]. A recent report from a multi-year monitoring project of a mixed-used watershed showed that all ARG tested were detected in surface waters only when human fecal markers were also present [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…가축 분변을 처 리하는 과정에서 사라지지 않고 남아있던 잔류 항생제는 항생 제 내성균에 의해 우리 주변의 환경으로 전파되어 항생제 내 성의 발달을 촉진한다 [9]. 항생제 내성에 관한 선행 연구들에 서는 환경에서 분리된 항생제 내성균과 임상에서 분리된 항생 제 내성균이 가지고 있는 ARG의 염기서열이 높은 비율로 일 치하는 결과를 발표했으며 [10], 이는 환경 내 ARG가 가축 분 변에서 기원했다는 하나의 근거 자료로 이용되고 있다 [11,12]. ARG는 플라스미드, 인테그론(integron), 트랜스포존(transposon) 등의 이동성유전 인자(MGE; mobile genetic elements)에 의해 동종 혹은 이종간 전달될 수 있다 [13].…”
unclassified